Steps on how a phantom can be 3D printed and embedded within a medium suitable for training of ultrasound-guided procedures. Issue 3 (July 2017) - Young, J; Coles-Black, J; Chao, I; Barrington, MJ
Practice is required for acquiring procedural proficiency and this can be obtained from clinical practice, or more sensibly, having novices first practice the skill on an inanimate phantom or trainer. Commercially produced phantoms are expensive and 3D printing is becoming more cost effective. In our example, we have used a 3D-printed thoracic spine. This allows practitioners to improve their ultrasound-guided regional anesthesia needle imaging skills through deliberate practice. In this report, we describe in detail the requirements for producing a 3D-printed phantom comprising a 3D segment of thoracic spine set within a semi-solid medium.